The Depictions of Psychological Conflict In “Middlemarch” by George Eliot - Rashidova, Feruza (Indonesian Journal Publisher, 2024)
This article explores the portrayal of psychological conflict in George Eliot’s “Middlemarch”, focusing on the inner struggles of key characters, particularly Dorothea Brooke and Tertius Lydgate. Eliot's detailed psychological realism presents the complexity of human emotion, moral dilemmas, and internal battles with social expectations. The narrative examines how personal ambitions clash with societal roles, creating a web of inner turmoil that affects each character’s decision-making and development. Through close textual analysis, the article demonstrates how Eliot's use of free indirect discourse and deep psychological insight shapes the narrative and enhances the reader’s understanding of the characters’ moral struggles. By exploring these internal conflicts, the article aims to shed light on how Eliot’s work reflects broader questions about human agency, responsibility, and self-understanding in a rapidly changing society.